Pharmacokinetics, Pharmacodynamics, and Safety of Evocalcet (KHK7580), a Novel Calcimimetic Agent: An Open-Label, Single- and Multiple-Dose, Phase I Trial in Healthy Chinese Subjects - He X; Narushima K; Kojima M; Nagai C; Li K (Dove Medical Press, 2024)
Xuemei He,1 Kazuya Narushima,2 Masahiro Kojima,2 Chisato Nagai,2 Kexin Li1 1Clinical Trial Center, Beijing Hospital, National Center of Gerontology; Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing Key Laboratory of Assessment of Clinical Drugs Risk and Individual Application, Beijing, People's Republic of China; 2Research & Development Division, Kyowa Kirin Co., Ltd, Tokyo, JapanCorrespondence: Kexin Li, Clinical Trial Center, Beijing Hospital, National Center of Gerontology; Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing Key Laboratory of Assessment of Clinical Drugs Risk and Individual Application, Beijing, People's Republic of China, Email kexinli6202@163.comPurpose: This study explored the pharmacokinetics (PK), pharmacodynamics (PD), and safety of evocalcet (KHK7580), a new calcimimetic agent, in healthy Chinese subjects following single and multiple doses.Methods: This was a single-center, open-label phase I trial conducted in China. The study started from the single-dose cohorts (1, 3, 6, 12 mg evocalcet, step-by-step administration) and proceeded to the multiple-dose cohort (6 mg evocalcet once daily for eight days). Blood and urine samples were collected at the designated time points for pharmacokinetic and pharmacodynamic analysis. Safety was evaluated by treatment-emergent adverse events (TEAEs), clinical laboratory tests, vital signs, electrocardiograms (ECGs), and ophthalmological examination.Results: Among 42 enrolled subjects, eight in each single-dose cohort and 10 in multiple-dose cohort, 40 subjects completed the study. In single-dose cohorts, tmax was 1.00- 2.00 h and declined biphasically. The mean t1/2 was 15.99- 20.84 h. Evocalcet exposure in AUC0-inf, AUC0-t, and Cmax showed a dose-proportional increase. In the multiple-dose cohort, tmax was 2.00 h and declined biphasically after multiple administrations. The accumulation was negligible. Ctrough levels were similar across days and steady from 24 hours after the first administration. The mean t1/2 was 15.59 h. PD analysis showed that evocalcet decreased intact parathyroid hormone and corrected calcium levels in a dose-dependent manner. Seventeen (40.5%) subjects reported TEAEs. No serious or severe TEAE occurred.Conclusion: In healthy Chinese subjects, evocalcet demonstrated dose-dependent PK and PD properties and was well-tolerated.Keywords: evocalcet, calcimimetic agents, secondary hypoparathyroidism, pharmacokinetic, pharmacodynamic, safety